LANDSCAPE LINGUISTICS OF PUBLIC PLACES IN LABUHANBATU UTARA - Husna, Nidaul (LINGUISTIK TERAPAN, 2023)
This study aims define which languages predominate in the Labuhanbatu Utara landscape, how texts are used, and why the texts are used. The study also suggests that societies, stakeholders and governments value local languages (expressions of cultural identity) and the Indonesian language as national identities to communicate formally or informally, especially in public settings. A descriptive qualitative design was used for this research. Bogdan and Biklen (1992) said that qualitative research is descriptive, i.e., it explains what is happening and what the data reveals. The research data was taken from the writings displayed on the nameboard, roadmap, mosque, store, pamphlet, billboard, etc.. installed in the data source in Labuhanbatu Utara. The study's data collection techniques included observation and documenting. According to the study's findings, the Indonesian language and local language have been used more and more in the past, especially in the landscape of government areas.